INTERNET AND CROSS-CULTURAL COMMUNICATION TO GENERATION Z - Andryani Sihombing, Indah; Mono, Umar; Perangin-angin, Alemina Br. (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Generation Z can be regarded as a generation that since they were born have grown up with the internet. The digital generation's reliance on information and communication technologies in both personal and professional affairs may be at an all-time high. Because they are